Ghostcatching and After Ghostcatching, Dances in the Dark - Barber, Tiffany E. (Dance research journal, 2015)
In 1999, Bill T. Jones, in collaboration with digital artists Paul Kaiser and Shelley Eshkar, presented an installation at the intersection of dance, drawing, and digital imaging. Ghostcatching featured Jones's previously improvised movements recorded using motion capture technology. In 2010, Kaiser, Eshkar, and Marc Downie of the OpenEndedGroup revised Ghostcatching into a new piece titled After Ghostcatching, composed of unused sequences of Jones's movement and sound captured for Ghostcatching. This essay focuses on the extended relation between Ghostcatching and After Ghostcatching to track a shift from so-called identity politics to a discourse of post-racialism over a ten-year period in U.S. history. A consideration of various media—motion capture technology, digital art and imaging, and improvised, virtual dance—as well as formal analysis of each piece, highlight the political effects and visual implications of each work in a racially mediated world. In this article, I question the status of Jones's raced, sexed, and gendered body within neoliberal fantasies of post-racialism. In spite of the persistence of visible markers such as skin color that are mobilized to construct racial subjects, with the development of digital imaging and new visual technologies, to what degree is race actually visual? That is, how are race and the racialized body in motion subject to and determined by specific media, i.e., photography and digital art, improvised dance and choreographic form? This analysis of Ghostcatching and After Ghostcatching reveals how each piece tests the boundaries of choreographic form and digital imaging technologies as well as the category of race as inherently visual—a test that posits race as technology itself in visual, haptic, and spatial terms.